Clinical diagnosis in terms of insurance medicine - Denisova Т.Р.; Lipatova Т.Е.; Malinova L.I.; Tyultyaeva L.A.; Kovalev Е.Р.; Alipova L.N.; Vakhlyueva O.G. (Саратовский научно-медицинский журнал, 2018)
Medical institutions in the conditions of insurance medicine are faced with not always justified interference of insurance companies in the structure of diagnosis and diagnostic process, whose violate the essence of the concepts of clinical classifications and statistical coding of diagnoses provided by ICD-10. Such a situation ultimately harms the patient and society, makes it difficult both to monitorthe adequacy of the ongoing treatment activities, and to protect the patient's rights to receive qualified medical care and doctor's rights.